A theoretical description of the first-forbidden ?-decay transitions within Pyatov's restoration method - uenlue, Serdar; BIrcan, Hasan; cakmak, Necla; Selam, Cevad (Indian Acad Sciences, 2023)
We describe the first-forbidden beta transitions by using Pyatov's restoration method within the framework of proton-neutron quasiparticle random phase approximation (pn-QRPA). A detailed formalism related to how to obtain the energies and wave functions of the first-forbidden excitations is clearly given in the present work. A comparison of the calculated results for various nuclei with the corresponding experimental data is given to demonstrate an application of the present approximation.
Keywords: Restoration; First-Forbidden Beta Transition; Proton-Neutron Quasiparticle Random Phase Approximation; Nuclear-Data Sheets; Isobar Analog Resonances; Broken Su(4) Symmetry; Pairing Correlations; Isospin Admixture; Shell-Model; Ge-76; Excitations; Suppression; Te-128